FUNCTIONAL FEATURE OF THE THYROID GLAND IN METABOLIC SYNDROME (OBESITY). (World Bulletin of Public Health, 2024)
Metabolic syndrome (MS) is a very serious pathological condition encountered in the work of doctors of various specialties. Often the presence of MS aggravates the normal functioning of the thyroid gland, as well as the occurrence of a number of diseases, while various diseases can serve as a risk factor for its development. The relevance of MS determines the need for its early diagnosis for timely correction and prevention of its long-term complications.
Keywords: Metabolic syndrome; thyroid gland; diagnosis